2017
DOI: 10.1177/1363460716678561
|View full text |Cite
|
Sign up to set email alerts
|

‘Straight with a pinch of bi’: The construction of heterosexuality as an elastic category among adult US men

Abstract: The sexualities of men who have same-sex desires yet identify as straight have attracted significant attention in recent years. We present findings from interviews with 100 such men, whom we recruited while they were seeking sex with men online, and examine the logics that allow them to maintain an identity as straight. Our sample is somewhat unique in that it included men across a wide age range (from 18 to 70), and also because many of our participants are white adult US men who are married or in stable rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 24 publications
1
67
1
Order By: Relevance
“…Over half a century later, we are at last beginning to fully acknowledge this view. Hammack DOI: 10.1159/000486469 Challenges to the idea of a binary sexual identity for men have come primarily from recent studies of straight-identified men who acknowledge same-sex desire and engage in same-sex behavior [e.g., Carrillo & Hoffman, 2018;Silva, 2017;Ward, 2015], including a considerable amount of research conducted by Savin-Williams and his colleagues [e.g., Savin-Williams, 2017Savin-Williams & Vrangalova, 2013]. An increasing body of evidence reveals the extent to which categorical notions of male sexuality fail to capture the empirical reality of men's sexual desire as fluid and far more complex than a simple binary taxonomy would suggest [see also SavinWilliams, 2014].…”
Section: "Sheep" and "Goats" No More? Challenging A Binary Conceptionmentioning
confidence: 99%
“…Over half a century later, we are at last beginning to fully acknowledge this view. Hammack DOI: 10.1159/000486469 Challenges to the idea of a binary sexual identity for men have come primarily from recent studies of straight-identified men who acknowledge same-sex desire and engage in same-sex behavior [e.g., Carrillo & Hoffman, 2018;Silva, 2017;Ward, 2015], including a considerable amount of research conducted by Savin-Williams and his colleagues [e.g., Savin-Williams, 2017Savin-Williams & Vrangalova, 2013]. An increasing body of evidence reveals the extent to which categorical notions of male sexuality fail to capture the empirical reality of men's sexual desire as fluid and far more complex than a simple binary taxonomy would suggest [see also SavinWilliams, 2014].…”
Section: "Sheep" and "Goats" No More? Challenging A Binary Conceptionmentioning
confidence: 99%
“…Many also do so in private. Maintaining a heterosexual identity allows them to enjoy the privileges that come with being recognized as heterosexual (Carrillo & Hoffman, 2018 For others, identifying as heterosexual is less a strategic decision and more a reflection of internalized homophobia (e.g., Miller et al, 2005;Reback & Larkins, 2010;Stokes & Peterson, 1998;Wolitski et al, 2006). The fact that some men continue to identify as heterosexual despite acknowledging or even acting upon same-sex desires suggests that they may experience feelings of shame or guilt brought on by negative attitudes toward same-sex sexuality.…”
Section: Heterosexually Identified Men's Experiences With Same-sex mentioning
confidence: 99%
“…In their day-to-day lives, they are attracted to and mostly have sex with women, not men. Sex with men only becomes desirable when they are unable to find female sexual partners (Carrillo & Hoffman, 2018;Reback & Larkins, 2010;Silva, 2018). Although men who have sex with other men, even infrequently, might conceivably identify as bisexual, most continue to identify as heterosexual because they assume that bisexuality requires a stronger, more frequent attraction to men (Carrillo & Hoffman, 2018).…”
Section: Heterosexually Identified Men's Experiences With Same-sex mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas I once (2008) theorized that a 'one-time rule of homosexuality' existed for men in the 1980s and 1990s, so that any sexual activity with another male socially coded him as homosexual, a 2017 special edition of the journal Sexualities documents the ways in which heterosexuality is also expanding to include a more expansive set of same-sex sexual behaviours (McCormack, 2017). Heterosexual men are, for example, engaging in male-male-threesomes (Scoats, Joseph, & Anderson, 2017), enjoying their own anal eroticism (Branfman, Stiritz, & Anderson, 2017) and having sexual intercourse with other men without having it question their own sexual identity as straight (Carrillo & Hoffman, 2017;Savin-Williams, 2017). Thus, it is evident that inclusive masculinities are not just about how males act towards each other, or what artistic, athletic, aesthetic, entertainment, occupational, or other aspects of social life they are culturally permitted or thwarted from engaging with; it is also about what sexual and semi-sexual behaviours they are culturally permitted to engage in.…”
Section: Eric Andersonmentioning
confidence: 99%